PUBLIC ENGAGEMENT OF ASEAN ECONOMIC COMMUNITY (AEC) ISSUE IN TWITTER ACCOUNT OF MINISTRY OF FOREIGN AFFAIR, REPUBLIC OF INDONESIA - Andari Karina Anom; Hana Hetty Manuela (Journal of Business Strategy and Execution, 2018)
The purpose of this research was to analyze public engagement on the issue of ASEAN Economic Community (AEC) in the Twitter account of Ministry of Foreign Affair, Republic of Indonesia. AEC is a single market and community across South East Asia started in 2016. As a member of Association of South East Asia Nations (ASEAN), Indonesia must disseminate information about AEC to its citizen. In term of population, Indonesia is the biggest in the region which make it affected more by this new policy. AEC is a good opportunity to increase quality of human resources to compete in global level. On the contrary, it could also be seen as a “threat” for the locals as they will not only compete with people from Indonesia, but also from other ASEAN countries. In term of economy, free market helps small medium enterprise to level up their business to regional level.  The research has specifically analyzed data from Twitter account @Portal_Kemlu-RI. Data were collected using Twitter analytic tools of the account from November 2015 to January 2016. The result indicates that different channel should use different approaches depend on the target audience. There should also be collaboration across institution to disseminate information about AEC since it involved many aspects.